Profile of an occupation – general nurse - Schambeck, Arne [Verfasser] (My University, 2022)
"The occupational profile of “general nurse” was introduced in 2020 to bring together the fields of geriatric nursing, general nursing and paediatric nursing with the aim of increasing the quality and attractiveness of nursing training. Those completing this generalist training programme are qualified to care for persons of all ages. New medical modules offered at the end of nursing training allow expanded competencies to be acquired." (BIBB-Doku)
Keywords: S 6.4.5 Gesundheits-, Sozial- und Erziehungsberufe; 370; Pflegeberuf; Berufsausbildung; Pflegefachmann; Tätigkeitsmerkmal